2013
DOI: 10.1001/jamaoto.2013.38
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of a Transnasal Flexible Fiberoptic In-Office Laryngeal Biopsy

Abstract: Importance: Transnasal fiberoptic laryngoscopy (TFL) has been used to guide various in-office procedures for the past 3 decades. Publications on in-office laryngeal biopsy have concurred that this procedure is safe, feasible, and easy to perform. However, the accuracy of inoffice biopsy via TFL has not yet been established. The aim of this study was to examine this issue.Objective: To compare pathologic results obtained via in-office TFL with those of subsequent direct laryngoscopy to assess the accuracy of TF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 22 publications
5
54
1
Order By: Relevance
“…Naidu et al evaluated a series of patients undergoing transnasal in‐office biopsy of laryngopharyngeal tumors and reported no complications . Similarly, Cohen et al reported no complications in a study of 102 patients undergoing transnasal in‐office biopsy for suspicious laryngeal lesions . In our study, there were no complications in 116 patients.…”
Section: Discussionsupporting
confidence: 71%
“…Naidu et al evaluated a series of patients undergoing transnasal in‐office biopsy of laryngopharyngeal tumors and reported no complications . Similarly, Cohen et al reported no complications in a study of 102 patients undergoing transnasal in‐office biopsy for suspicious laryngeal lesions . In our study, there were no complications in 116 patients.…”
Section: Discussionsupporting
confidence: 71%
“…Only 15% of invasive SCC was identified at office biopsy, and it is evident that any clinically suspicious neoplasm must be evaluated with direct microlaryngoscopy as possible. Cohen et al noted a 33% false negative rate of in‐office flexible laryngeal biopsy; and in their series, CIS on office biopsy was most often SCC at DML . It should be noted, however, that when an office biopsy showed a diagnosis of SCC, it was correlated with the final histologic diagnosis in 100% of patients.…”
Section: Discussionmentioning
confidence: 88%
“…Due to the relative novelty of this office-based procedure, few studies are available and complication rates have been assessed in small sample sizes [6, 7, 1214, 19]. Therefore, the aim of this study was to investigate the complications of transnasal FEB under topical anesthesia in patients with benign and malignant laryngopharyngeal lesions.…”
Section: Introductionmentioning
confidence: 99%